Influence of nafen nanoparticles on the strength of nickel. (December 2020) - Agureev, L E; Ivanov, B S; Savushkina, S V; Laptev, I N; Kanushkin, A I; Sivtsova, G V
Abstract: The article presents the results of studies of the structure and properties of pure nickel with the addition of nanofibers of aluminum oxide – nafen. The samples were obtained by spark plasma sintering of mechanically activated metal powder. The effect of nanofibers on Young's modulus and ultimate strength of nickel at 25 °C and elevated temperatures is considered.